2022
DOI: 10.1177/10468781221113030
|View full text |Cite
|
Sign up to set email alerts
|

Same Gaming: An Exploration of Relationships Between Gender Traits, Sexual Orientation, Motivations, and Enjoyment of Playing Video Games

Abstract: Introduction Existing research has focused on sex and gender to explain video games playing motivations and enjoyment. This study investigated gender traits and sexual orientation to further explain why people play games and what leads to gaming enjoyment. Methods Participants ( N = 198) answered questions on gender traits (positive/negative feminity/masculinity), gaming motivations, enjoyment, sexual orientation (32.0% of the sample belonged to the lesbian, gay, and bisexual community, later LGB community), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 64 publications
0
5
0
1
Order By: Relevance
“…Asimismo, Akel et al (2023), en un estudio desarrollado en jóvenes libaneses, reveló que los varones tienen una mayor exposición a VG violentos y una mayor aprobación de la agresión, ansiedad, insomnio y dependencia. Ahora bien, a pesar de que los videojuegos son más practicados por varones (Yao et al, 2022), en los últimos años existe un crecimiento considerable de mujeres que desarrollan dependencia a videojuegos (Aleissa et al, 2022;Kneer et al, 2022).…”
Section: Discusión Y Conclusionesunclassified
“…Asimismo, Akel et al (2023), en un estudio desarrollado en jóvenes libaneses, reveló que los varones tienen una mayor exposición a VG violentos y una mayor aprobación de la agresión, ansiedad, insomnio y dependencia. Ahora bien, a pesar de que los videojuegos son más practicados por varones (Yao et al, 2022), en los últimos años existe un crecimiento considerable de mujeres que desarrollan dependencia a videojuegos (Aleissa et al, 2022;Kneer et al, 2022).…”
Section: Discusión Y Conclusionesunclassified
“…Avatars provide users with options for identity expression, such as the ability to walk, run, fly, and even teleport [ 75 ]. Several studies in the field of player experience have demonstrated a positive correlation between AU and PE [ 76 , 77 , 78 ]. This relationship has also been verified in non-pure entertainment environments; for instance, in e-learning, AU has been linked to enjoyment of the experience [ 79 ] and perceived enjoyment of human computation games [ 80 ].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…It is when tensions are high, that gamers tend to be more aggressive with their words. As an example, "men seem to play games more in general and exhibit problematic gaming behavior more frequently, whereas women play games for social reasons more often" (Kneer et al, 2022). Women can also show these signs of aggression as well and cause harassment to the community that surrounds them but it is the language and saying that men use that make it different from other forms.…”
Section: Sexual Harassment In the Communitymentioning
confidence: 99%